2012
DOI: 10.1071/wf11092
|View full text |Cite
|
Sign up to set email alerts
|

Fire effects on the spatial patterning of soil properties in sagebrush steppe, USA: a meta-analysis

Abstract: Understanding effects of changes in ecological disturbance regimes on soil properties, and capacity of soil properties to resist disturbance, is important for assessing ecological condition. In this meta-analysis, we examined the resilience of surface soil properties and their spatial patterning to disturbance by fire in sagebrush steppe of North America – a biome currently experiencing increases in wildfire due to climate change. We reviewed 39 studies that reported on soil properties for sagebrush steppe wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 70 publications
1
60
1
Order By: Relevance
“…However, today up to 48 percent of these big sagebrush ecosystems have been modified as a result of accidental or intentional fire, conversion to dominance by invasive species, intentional shrub removal to improve perennial grass forage, conversion to cropland, and exurban or energy development (Knick et al 2003, Connelly et al 2004, Sankey et al 2012. Energy development in the form of oil and gas production first occurred early in the 20th century and has recently increased rapidly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, today up to 48 percent of these big sagebrush ecosystems have been modified as a result of accidental or intentional fire, conversion to dominance by invasive species, intentional shrub removal to improve perennial grass forage, conversion to cropland, and exurban or energy development (Knick et al 2003, Connelly et al 2004, Sankey et al 2012. Energy development in the form of oil and gas production first occurred early in the 20th century and has recently increased rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…The type of disturbance (e.g., fire, shrub removal, land use change), the pre-disturbance plant community including subspecies of big sagebrush, soil conditions, and climatic conditions during big sagebrush reestablishment all influence the recovery of big sagebrush plant communities (Anderson and Inouye 2001). For example, disturbances such as fire affect surface soil characteristics of shrub and intershrub microsites and thereby can influence plant community recovery (Sankey et al 2012). Watts and Wambolt (1996) studied recovery in four different types of disturbance treatments, and their results suggested that Wyoming big sagebrush plant communities recover at different rates depending upon disturbance type.…”
Section: Introductionmentioning
confidence: 99%
“…This fine-scale heterogeneity in soil organic matter, which is concentrated under individual shrubs relative to interspaces, is a well-recognized feature of sagebrush ecosystems, with indications that it is responsive to changes in ecosystem management (Burke et al 1987, Sankey et al 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…For example, deposition of soil and litter under shrubs can create more porous conditions that increase infiltration and water availability for shrubs (Stavi et al 2009). Although resource islands are common in many arid and semi-arid ecosystems around the world, their role in either degradation or stability of ecosystems can differ (Stavi et al 2009, Sankey et al 2012. In arid grassland systems, formation of resource islands is recognized as a form of degradation resulting from woody-shrub encroachment into grasslands where soil nutrients were previously more homogenous (Schlesinger et al 1990, Stavi et al 2009, Ravi et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…With under-shrub and interspace differences playing such a central part in Artemisia ecosystem functioning, management practices that disturb the soil (e.g., seeding, chaining, and amendments) and possibly alter this heterogeneity need to be explored to determine how they affect ecosystem resilience (Charley and West 1975, Sankey et al 2012. However, little is known about the duration of time necessary for resource islands to reform after soils are homogenized by human disturbance.…”
Section: Introductionmentioning
confidence: 99%